Construction of Financial Management Information System Model in Colleges and Universities Based on Data Mining Algorithm - Wang, Xinyuan (International Conference on Measuring Technology and Mechatronics Automation (Print), 2019)
Financial management is an important link in the financial management of colleges and universities. On the basis of the analysis of the defects in the traditional financial management methods, the financial management theory and the early warning theory of the colleges and universities are combined in this paper. The data mining algorithm is applied to establish the financial management information system model of the colleges and universities. Firstly, A universities in both Shanghai City and Shenzhen City in the recent two years are taken as the research subjects. The colleges and universities that are included in the special treatment due to the abnormal financial situation are defined as the financial crisis sign for the colleges and universities. In addition, the financial data in the annual report of the colleges and universities are adopted as the input feature vector, and then the data mining algorithm is combined with the data mining to establish a kind of financial management information system model of the colleges and universities through the empirical methods. The empirical results have verified the effectiveness of the model put forward in this paper.